WANITA DI ANTARA KERJA DAN RUMAH TANGGA (STUDI KASUS PADA BURUH WANITA INDUSTRI JAMUR DI DESA HARGOBINANGUN KECAMATAN PAKEM KABUPATEN SLEMAN DIY) - Noviarina Purnami Putri; Ken Suratiyah; Suhatmini Hardyastuti (PIRAMIDA, 2007)
In term of development, women often contribute significant role. As potential resource, their dynamic action will be further close to the goals of development. Our country holds the big project which entirely supported by its people, named women empowerment. The increasing of women labor forced indicate their active participation. This demographic trend made women has multiply role as worker and housewife. This research purpose to know how women share their time for the economic ad household activity and its relations with work-and family conflict. This study was conducted at Hargobinangun village, Pakem sub-district, Sleman district. Data collected by interviewing 30 women workers of mushroom home industries. The result shows that there is no significant difference among women workers to allocate their time for economic and household activities. Women workers allocated their time to do economic activities in fact have no significant correlation with work ? family conflict. And also there is no significant correlation between their allocated time to do household activities and family ? work conflict.